A prevalence study of primary dystonia in eight European countries. - Epidemiological Study of Dystonia in Europe (ESDE) Collaborative Group (2000)
There have been few epidemiological studies of dystonia. Most previous studies have provided estimates based on few cases. A European prevalence study was undertaken to provide more precise rates of dystonia by pooling data from eight European countries. Diagnosed cases were ascertained by adult neurologists with specialist movement disorder (and botulinum toxin) clinics. The crude annual period prevalence rate (1996-1997) for primary dystonia was 152 per million (95% confidence interval 142-162), with focal dystonia having the highest rate of 117 per million (108-126). Prevalence rates for cervical dystonia, blepharospasm and writer's cramp were as follows: 57 (95% confidence interval 51-63), 36 (31-41), and 14 (11-17). The age-adjusted relative rates were significantly higher in women than in men for segmental and focal dystonias with the exception of writer's cramp. Comparing rates between centres demonstrated significant variations for cervical dystonia, blepharospasm and writer's cramp, probably due to methodological differences. Our results provide the first data on the prevalence of primary dystonia and its subtypes across several European countries. Due to under-ascertainment of cases, our rates should be seen as conservative and an under-estimate of the true prevalence of dystonia.